Experimental and numerical study on 3D printing stainless steel I-section columns subject to compressive loading - San, Bing-Bing; Huang, Lei; Shan, Zhi-Wei; Zhao, Wen-Hui (Structures (Oxford), 2025)
This paper presents an experimental investigation on the material properties and mechanical behavior of 316 L stainless steel I-section stub columns additively manufactured using laser powder bed fusion (LPBF). A total of 42 tensile coupons and 6 stub columns were fabricated using 316 L stainless steel powders by the LPBF technique. 36 rectangular plates and 6 directly formed specimens were used for tensile tests to evaluate the effects of the coupon specimen orientations, thicknesses and scanning strategies on the mechanical properties. It indicated the tensile strength increased with the increase of the coupon thickness. The specimen with a 45° orientation fabricated using the bidirectional scanning strategy (S1) exhibits a higher degree of strain hardening, and its strength is significantly greater than that of the specimens oriented at 0° and 90°. In addition, local geometric imperfections of the stub columns were measured before the compressive tests. The failure modes, ultimate load-bearing capacities and structural responses of the stub columns with three different cross-sections subject to axial compression were obtained and analysed. It was found that the failure mode of the stub columns was local buckling. As the axial deformation increased, buckling occurred in the upper part of the columns for all specimens, where noticeable lateral deformations were observed in the flanges and webs. The effectiveness of design methods recommended in existing design specifications was studied. It can be concluded that the continuous strength method (CSM) can accurately predict the ultimate bearing capacities of LPBF-formed 316 L stainless steel stub columns.